2005
DOI: 10.1182/blood-2005-03-1047
|View full text |Cite
|
Sign up to set email alerts
|

Platelet NAD(P)H-oxidase–generated ROS production regulates αIIbβ3-integrin activation independent of the NO/cGMP pathway

Abstract: Platelets play a crucial role in the physiology of primary hemostasis and pathophysiologic processes such as arterial thrombosis. Accumulating evidence suggests a role of reactive oxygen species (ROSs) in platelet activation. Here we show that platelets activated with different agonists produced intracellular ROSs, which were reduced by reduced nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) oxidase inhibitors and superoxide scavengers. In addition, we demonstrate that ROSs produced in platelets signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
160
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(177 citation statements)
references
References 23 publications
12
160
2
3
Order By: Relevance
“…In control experiments, we found that NOX2 deletion or catalase treatment reduced intracellular ROS generation in both resting and activated mouse platelets and that compared with NOX2 deletion, treatment of NOX2 KO platelets with catalase further decreased ROS production (supplemental Figure 3A), implying that other pathways may also generate ROS. Consistent with previous studies, 13 extracellular ROS were not detected in activated platelets (data not shown). These results suggest that platelet NOX2-generated ROS such as H 2 O 2 regulate P-selectin exposure induced by submaximal concentrations of thrombin.…”
Section: Platelet Nox2 Regulates P-selectin Exposure Upon Agonist Stisupporting
confidence: 93%
See 2 more Smart Citations
“…In control experiments, we found that NOX2 deletion or catalase treatment reduced intracellular ROS generation in both resting and activated mouse platelets and that compared with NOX2 deletion, treatment of NOX2 KO platelets with catalase further decreased ROS production (supplemental Figure 3A), implying that other pathways may also generate ROS. Consistent with previous studies, 13 extracellular ROS were not detected in activated platelets (data not shown). These results suggest that platelet NOX2-generated ROS such as H 2 O 2 regulate P-selectin exposure induced by submaximal concentrations of thrombin.…”
Section: Platelet Nox2 Regulates P-selectin Exposure Upon Agonist Stisupporting
confidence: 93%
“…12 However, NOX5 is expressed only in the vasculature of humans. Compared with platelets that produce low amounts of ROS through NOX1 and NOX2, 13,14 neutrophils rapidly generate much larger amounts of ROS via NOX2 after cell activation. 15 The NOX2 enzyme consists of membrane subunits (p22 phox and gp91 phox ) and cytosolic components (p47 phox , p67 phox , p40 phox , and small GTPase Rac1/2), and generates O 2 ·-by transferring 1 electron from NADPH to molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 NAD(P)H oxidase inhibitors and superoxide scavengers also reduce platelet aggregation and thrombus formation on collagen. 22 Collagen also induces NAD(P)H oxidase-dependent superoxide release in platelets, which in turn enhances availability of released ADP, resulting in increased platelet recruitment. 23 Consistent with these studies, platelets from gp91 phox -deficient patients produce only a small amount of reactive oxygen species.…”
Section: Reactive Oxygen Species and Platelet Functionmentioning
confidence: 99%
“…In contrast, there are several studies demonstrating that CS actually reduces the oxidantproducing capacity of neutrophils while elevating adhesion molecule expression (17,18), although less is known about monocytes and lymphocytes. With the recent abundance in the literature on the interactions between the inflammatory and thrombogenic pathways induced in many disease states, it would be interesting to determine whether platelets, which are activated by CS (4,6) and can themselves produce superoxide from NAD(P)H oxidase (3,7,13), participate in the vascular oxidative stress and inflammation generated during smoking.…”
mentioning
confidence: 99%